Pengaruh Corporate Social Responsibility terhadap Nilai Perusahaan dengan Profitabilitas dan Leverage Sebagai Variabel Pemoderasi - Meilinda Murnita, Putu Elia; Dwiana Putra, I Made Pande (E-Jurnal Akuntansi; Vol 23 No 2 (2018), 2018)
This study aims to determine the effect of corporate social responsibility on corporate value with profitability and leverage as a moderating variable in manufacturing companies. This research was conducted at manufacturing company listed on BEI year 2014-2016. The sample of this research is 22 companies for 3 consecutive year, so total sample counted 66 sample with method of determination of sample by using purposive sampling method. Data analysis techniques used are simple linear regression analysis and Moderated Regression Analysis (MRA) to test the hypothesis. Based on the results of this study indicate that corporate social responsibility variable has a positive effect on firm value. Profitability strengthens the influence of corporate social responsibility on corporate value. Leverage variables weaken the impact of corporate social responsibility on corporate value.